Characterization of the Percival detector with soft X‐rays. (26th November 2020) - Marras, Alessandro; Correa, Jonathan; Lange, Sabine; Vardanyan, Vahagn; Gerhardt, Tim; Kuhn, Manuela; Krivan, Frantisek; Shevyakov, Igor; Zimmer, Manfred; Hoesch, Moritz; Bagschik, Kai; Scholz, Frank; et al.
Abstract : Characterization of the Percival 2Megapixel detector with soft X‐rays is presented. Abstract : In this paper the back‐side‐illuminated Percival 2‐Megapixel (P2M) detector is presented, along with its characterization by means of optical and X‐ray photons. For the first time, the response of the system to soft X‐rays (250 eV to 1 keV) is presented. The main performance parameters of the first detector are measured, assessing the capabilities in terms of noise, dynamic range and single‐photon discrimination capability. Present limitations and coming improvements are discussed.